Records of Boeckella poppei (Mrazek, 1901) (Calanoida: Centropagidae) obtained during Ukrainian Antarctic Expeditions - Nabokin, M.; Salganskiy, O.; Tkachenko, V.; Kovalenko, P.; Dzhulai, A.; Puhovkin, .A.; Gogol, S.; Protsenko, Yu.; Svetlichniy, L.; Kozeretska, I. (Ukrainian Antarctic Journal, 2023)
The copepod Boeckella poppei (Mrazek, 1901) (Calanoida: Centropagidae) is one of the Maritime Antarctic’s most common freshwater zooplankton species. It was first discovered in 1961–1962 on Signy Island (South Orkney Islands). Nowadays, it is found on many other islands in the region. The copepod is also found on Western Subantarctic islands, in the eastern part of the continent, and South America. However, in the Wilhelm Archipelago, there have been only a few disjointed findings of the species so far: it has been noted as numerous both north and south of the Ukrainian Antarctic Akademik Vernadsky station, yet for the archipelago, there are only two brief records which do not describe its distribution in this region. Our data are based on 114 specimens collected in 2005–2023 during Ukrainian Antarctic Expeditions. Boeckella poppei was found in 51 samples from 23 lakes on eight islands: Uruguay, Irizar, Berthelot, Galindez, Roca, and Eight (Wilhelm Archipelago), Nelson, King George (South Shetland Islands). Live specimens were recorded during the ice-free period and significantly after the surface was frozen. In many samples, adults and copepodid stages were found, while nauplii were not found.